1993
DOI: 10.1148/radiology.188.2.8327714
|View full text |Cite
|
Sign up to set email alerts
|

Gamekeeper thumb: differentiation of nondisplaced and displaced tears of the ulnar collateral ligament with MR imaging. Work in progress.

Abstract: Ulnar collateral ligament (UCL) injury of the first metacarpophalangeal joint (gamekeeper thumb) is common. If the UCL becomes displaced superficially to the adductor pollicis aponeurosis, surgical treatment has been advocated. Radiography cannot help differentiate between displaced and nondisplaced tears. The authors investigated the use of magnetic resonance (MR) imaging in the evaluation of UCL injury. Ten displaced and six nondisplaced UCL tears were surgically created in 16 nonembalmed cadaveric specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 0 publications
0
33
0
3
Order By: Relevance
“…28 Studies using MRI to detect UCL injuries found that MRI yielded sensitivity of 96% to 100% and specificity of 94% to 100% for the detection of Stener lesions. 23,28 The accuracy of MRI has led to the development of a new classification guide for UCL management based on MRI scans displaying distance of UCL displacement in millimeters. 18 A recent treatment-oriented classification proposed by Milner 18 suggests surgery for all ruptured ligaments demonstrating displacement of 3 mm or greater (type 3) as well as those appearing to have a Stener lesion (type 4).…”
Section: Late Years (1990s To Present)mentioning
confidence: 99%
“…28 Studies using MRI to detect UCL injuries found that MRI yielded sensitivity of 96% to 100% and specificity of 94% to 100% for the detection of Stener lesions. 23,28 The accuracy of MRI has led to the development of a new classification guide for UCL management based on MRI scans displaying distance of UCL displacement in millimeters. 18 A recent treatment-oriented classification proposed by Milner 18 suggests surgery for all ruptured ligaments demonstrating displacement of 3 mm or greater (type 3) as well as those appearing to have a Stener lesion (type 4).…”
Section: Late Years (1990s To Present)mentioning
confidence: 99%
“…Recently, it has been reported that MRI may serve as a useful diagnostic tool for the evaluation of UCL tears. Results of 100% sensitivity and 94% specificity in depicting Stener lesions have been reported in a cadaveric study [9]. The present study was designed to assess the value of MRI in the detection of Stener lesions in the cadaveric model.…”
mentioning
confidence: 92%
“…Thus, the tom ligament can become trapped by the aponeurosis and folded over to point proximally, when the abduction force is released (Stener 1962). Closed treatment is adequate for nondisplaced ruptures (Newland 1992, Spaeth et at. 1993) whereas for ruptures with displacement superficial to the adductor aponeurosis, surgical treatment is advocated (Louis et al 1986, Wilhelm et al 1989.…”
Section: Discussionmentioning
confidence: 99%
“…(Abrahamsson et a1.1990). However, Louis et al (1986) and Spaeth et al (1993) have proposed that displacement of a ruptured but nondisplaced ligament may occur during stability testing. Bronstein et al…”
Section: Discussionmentioning
confidence: 99%